Colonization of Actinomycetes Encapsulates in The Rhizosphere of Cultivated Plants - Dama, Dewi Rahayu; Retnowati, Yuliana; Kandowangko, Novri Youla; Katili, Abubakar Sidik; Ahmad, Jusna (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The growth of cultivated plants is often hampered by soil degradation due to excessive use of chemical inputs. The use of microorganisms such as actinomycetes offers an environmentally friendly alternative, but its appli cation is still limited due to its low viability in the field. This study aims to analyze the colonization ability of encapsulated actinomycetes on the roots of cultivated plants, focusing on parameters such as the ability to infect root tissue, and the ability to induce growth in cultivated plants. Actinomycete isolates were obtained from the rhizosphere of maize plants that exhibit PGPR activity. This study was conducted quantitatively with a descriptive approach. This study used treatments with and without inoculation of encapsulated actinomycetes on maize (Zea mays var. ceratina) and cocoa (Theobroma cacao) plants. The results showed that encapsulated actinomycetes were able to colonize the root systems of maize and cocoa plants, as indicated by the presence of actinomycete filamentous structures on the root surface and within the root tissue. Inoculation with encapsulated actinomycetes induced growth in both plant species, as demonstrated by improvements in all growth parameters. Encapsulated actinomycetes have the potential to be effective biological agents for enhancing plant growth and provide an environmentally friendly technological alternative to support sustainable agriculture.